Comparative Evaluation of Fe-MOF, Cu-MOF, and Bimetallic Fe/Cu-MOF for Enhanced CO₂ Adsorption: Synthesis, Characterization, and Performance Analysis - Nor Khonisah Daud; Hamidah Abdullah; Nur Aminatulmimi Ismail (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Rising atmospheric CO₂ concentrations necessitate the development of efficient and economically viable carbon capture materials. Metal-organic frameworks (MOFs) offer strong potential due to their tunable pore structures and accessible metal sites. In this work, Fe-MOF, Cu-MOF, and bimetallic Fe/Cu-MOF were synthesized via a solvothermal route and systematically evaluated for CO₂ adsorption performance. The materials were characterized using SEM-EDX, FTIR, XRD, BET, and TGA to establish correlations between structural properties and adsorption behavior. CO₂ uptake was investigated under varying pressure (1-5 bar), adsorbent dosage (0.2-0.5 g), and temperature (40-50 °C). Among the three adsorbents, Fe/Cu-MOF exhibited the highest adsorption capacity, reaching 3.22 mg.g-¹ at 5 bar, outperforming Fe-MOF (2.54 mg.g-¹) and Cu-MOF (2.35 mg.g-¹). Adsorption increased markedly with pressure, showed non-linear dependence on dosage due to site underutilization and diffusion limitations, and decreased with increasing temperature, indicating an exothermic physisorption-dominated process. BET analysis revealed that Fe/Cu-MOF possessed the highest surface area (19.4 m².g-¹) and pore volume (0.0489 cm³.g-¹), while XRD and FTIR confirmed successful incorporation of both metal centers, generating chemically heterogeneous adsorption sites. Kinetic analysis demonstrated that CO₂ uptake follows a pseudo-first-order model, consistent with surface-controlled physisorption. The enhanced performance of Fe/Cu-MOF is attributed to synergistic effects arising from dual-metal coordination, improved pore connectivity, and increased availability of active adsorption domains. These findings highlight the potential of bimetallic Fe/Cu-MOFs as promising candidates for pressurized CO₂ capture applications and provide insight into structure-performance relationships governing gas adsorption in defect-rich MOF systems. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).